Bank Selection Influencing Factors: A Study on Customer Preferences with Reference to Rajshahi City - Siddique, Md. Nur-E-Alam (Asian Business Review, 2012)
This study analyses the factors considered important by customer in selection a private commercial bank and nationalized commercial bank in Bangladesh. It is based on a survey of 600 customers of private commercial banks (PCBs) and nationalized commercial banks (NCBs) located in the city of Rajshahi in Bangladesh. This study relied on 30 selection factors extracted from relevant literature, personal experience, and interviews with the some bank officials and customers. The findings reveal that the most important factors influencing customers for selecting a private commercial bank are effective and efficient customer services, speed and quality services; image of the bank, online banking, and well management. On the other hand, the most important factors for choosing a nationalized commercial bank are low interest rate on loan, convenient branch location, safe investment (accountability of the govt.), variety of services offered and low eservice charges. Findings also suggest that there are some of significant statistical differences between responses of PCB and NCB customers related to factors considered important in selection a bank.
Keywords: Bank Selection; Influencing Factor; Customer Preferences; Rajshahi City